2009
DOI: 10.1002/app.29942
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroalkyl end‐capped oligomer possessing a nonflammable characteristic in silica gel matrices even at 800°C under atmospheric conditions

Abstract: We succeeded in observing the similar solid‐state NMR spectra (1H‐magic‐angle spinning NMR spectra) of fluoroalkyl end‐capped N‐(1,1‐dimethyl‐3‐oxobutyl)acrylamide oligomer [RF‐(DOBAA)n‐RF]/silica gel nanocomposite before and even after calcinations at 800°C. This finding suggests that RF‐(DOBAA)n‐RF oligomer in RF‐(DOBAA)n‐RF/silica gel nanocomposite can afford a nonflammable characteristic to exhibit no weight loss behavior even at 800°C under atmospheric conditions. In addition, we had good oleo‐ and hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…In fact, we have already reported that the 1 H MAS NMR spectra of the R F -(DOBAA) n -R F /silica nanocomposite (with the oligomer content in the composite at 23%, as determined by elementary analyses of fluorine), which exhibit no weight loss even after calcinations at 800 1C, can exhibit similar relatively sharp peaks at around 50 to À20 p.p.m. 17 These peak areas are almost the same as those before calcination at 800 1C. 17 Furthermore, it was previously reported that hexafluorosilicic acid can interact smoothly with amido segments in N,N-dimethylformamide to give a stable hexafluorosilicic acid-N,N-dimethylformamide 1:3 adduct.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…In fact, we have already reported that the 1 H MAS NMR spectra of the R F -(DOBAA) n -R F /silica nanocomposite (with the oligomer content in the composite at 23%, as determined by elementary analyses of fluorine), which exhibit no weight loss even after calcinations at 800 1C, can exhibit similar relatively sharp peaks at around 50 to À20 p.p.m. 17 These peak areas are almost the same as those before calcination at 800 1C. 17 Furthermore, it was previously reported that hexafluorosilicic acid can interact smoothly with amido segments in N,N-dimethylformamide to give a stable hexafluorosilicic acid-N,N-dimethylformamide 1:3 adduct.…”
Section: Resultssupporting
confidence: 59%
“…17 These peak areas are almost the same as those before calcination at 800 1C. 17 Furthermore, it was previously reported that hexafluorosilicic acid can interact smoothly with amido segments in N,N-dimethylformamide to give a stable hexafluorosilicic acid-N,N-dimethylformamide 1:3 adduct. 18,19 Thus, the surface of smoothly encapsulated R F -(DOBAA) n -R F oligomer into silica gel nanomatrices through effective hydrogen bonding interactions of the amido protons in the oligomers and fluorines in ammonium Oligomer in composite Synthetic conditions Size of composite, nm (after calcination, nm) Weight loss (%) at 800 1C …”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Similarly, ammonium-type and imidazolium-type ionic liquids such as TEON-TFSI, TBMN-TFSI, and EMI-TFSI were able to afford no weight loss behavior toward the corresponding ionic liquid/SiO 2 nanocomposites even after calcinaton at 800°C. Previously, we reported that fluoroalkyl end-capped oligomers possessing amido protons or sulfo groups can suffer the sol-gel reactions with TEOS and silica nanoparticles in the presence of aqueous ammonia to afford the corresponding oligomer/ silica nanocomposites possessing no weight loss behavior even after calcination at 800°C [20][21][22][23][24][25][26][27][28]. Especially, these fluorinated oligomers can afford the smooth dehydrofluorination of amido protons or sulfonic acid protons with fluorines in oligomers catalyzed by ammonia and silica nanoparticles to afford ammonium hexafluorosilicate during the sol-gel process [20][21][22][23][24][25][26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that fluoroalkyl end-capped oligomers possessing amido protons or sulfo groups can suffer the sol-gel reactions with TEOS and silica nanoparticles in the presence of aqueous ammonia to afford the corresponding oligomer/ silica nanocomposites possessing no weight loss behavior even after calcination at 800°C [20][21][22][23][24][25][26][27][28]. Especially, these fluorinated oligomers can afford the smooth dehydrofluorination of amido protons or sulfonic acid protons with fluorines in oligomers catalyzed by ammonia and silica nanoparticles to afford ammonium hexafluorosilicate during the sol-gel process [20][21][22][23][24][25][26][27][28]. The surface of these smoothly encapsulated fluorinated oligomer into silica gel nanomatrices through the effective hydrogen bonding interactions between the amido protons or sulfonic acid protons in oligomers and fluorines in ammonium hexafluorosilicate could possess an extraordinarily high oxidation resistance to exhibit a nonflammable characteristic during the calcination process at 800°C [20][21][22][23][24][25][26][27][28].…”
Section: Resultsmentioning
confidence: 99%